The Effects of Andrographis paniculata on Platelet Activity in Healthy Thai Volunteers. (6th August 2018) - Sirikarin, Tichapa; Palo, Titchaporn; Chotewuttakorn, Sirikul; Chandranipapongse, Weerawadee; Limsuvan, Suveerawan; Akarasereenont, Pravit
Abstract : Background. Andrographis paniculata (AP) has been used in Thai traditional medicine to treat various infections, including the common cold and fever. Its bioactive compound, andrographolide, has shown antiplatelet activities in an in vitro study model. Since clinical studies of the effects of AP on the human platelet function have never been reported, we investigated its effect on platelet activity in ten healthy volunteers. Methods . Two grams of AP was taken 3 times within one day. The blood was withdrawn by venipuncture before and 2 and 24 hours after the AP administration to analyze the effects of AP on platelet aggregation, the expression of enzyme cyclooxygenase (COX) mRNA and protein, and TXB2, including P-selectin. Result . Even though there was no significant change in the studied parameters, this study exhibited patient-to-patient variability in platelet function. It was found that ADP-induced platelet aggregation tended to decrease after AP administration, while epinephrine-induced platelet aggregation in females tended to be higher than that in males for the entire study period. Moreover, COX-1 mRNA levels tended to decrease while P-selectin levels tended to rise after AP administration. Conclusion . These controversial results are possibly due to the multifactorial mechanisms of platelet aggregation as well as the multichemical composition of AP. Further study, probably at the molecular level, is needed to unveil the underlying mechanisms of action of AP.